Food habits and tourist food consumption: an exploratory study on dining behaviours of Chinese outbound tourists in Spain. Issue 1 (2nd January 2020) - Lin, Jiayi; Guia Julve, Jaume; Xu, Honggang; Cui, Qingming
ABSTRACT: Local food as a tourism attraction has been well recognized and studied by many tourism scholars. However, the phenomenon that tourists prefer food other than local food has not gotten much attention. This article attempts to explore how the eating habits of tourists can hinder their consumption of local food by studying the food consumption behaviours of Chinese tourists in Spain. Qualitative methods were employed to interview fifty-two Chinese tourists in Barcelona, and field notes of participant observations taken during thirteen familiarization trips for Chinese market were also used to help understand the dining behaviours of Chinese tourists. The results show that due to different food habits, Chinese tourists only sampled local Spanish food during their travels in Spain. The challenges to Chinese food habits included unfamiliar ingredients, strange tastes, different quantities of food, different dining times and duration, and different cultural concepts of healthy food. The research also reveals that Chinese tourists chose many strategies to deal with the unaccustomed eating situations, such as enduring the cultural differences, eating familiar fast food, eating just Chinese food, or bringing food from home. In long-haul Europe travels, Chinese tourists often switch among these strategies in order to eat healthily and comfortably.